Effect of Compaction Pressure on the Enzymatic Activity of Pancreatin in Directly Compressible Formulations - Daniel Zakowiecki; Peter Edinger; Tobias Hess; Jadwiga Paszkowska; Marcela Staniszewska; Svitlana Romanova; Grzegorz Garbacz (MDPI AG, 2023)
Tableting of biomolecules is a challenging formulation phase due to their sensitivity to various process parameters, such as compression pressure, process dynamics, or the temperature generated. In the present study, pancreatin was employed as a model enzyme mixture, which was formulated in tablet form utilizing the synergistic effects of brittle and plastic excipients (dibasic calcium phosphate and microcrystalline cellulose, respectively). The effect of varying compaction pressure and lubricant concentration on the generated temperature and enzymatic activity was evaluated. The tablets were analyzed for pancreatin content and the activity of two enzymes (protease and amylase) using pharmacopoeial tests. This study indicated that the formulations proposed here allow tableting over a wide range of compaction pressures without adversely affecting pancreatin content and its enzymatic activity.